2002
DOI: 10.1186/1471-2180-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cultured isolates of clinically important yeast species using fluorescent fragment length analysis of the amplified internally transcribed rRNA spacer 2 region

Abstract: Background: The number of patients with yeast infection has increased during the last years. Also the variety of species of clinical importance has increased. Correct species identification is often important for efficient therapy, but is currently mostly based on phenotypic features and is sometimes time-consuming and depends largely on the expertise of technicians. Therefore, we evaluated the feasibility of PCR-based amplification of the internally transcribed spacer region 2 (ITS2), followed by fragment siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Internal transcribed spacer (ITS) sequencing is considered as a rapid and accurate tool for identification of fungal pathogens [26]. Genetic variation within ITS region is considered to be sufficient for identification and typing of different fungal strains [27][28][29]. Azoles and allylamines (terbinafine) act as antifungal agents by inhibition of ergosterol biosynthesis while polyenes (nystatin) disrupt cell functions by binding to ergosterol in plasma membrane [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Internal transcribed spacer (ITS) sequencing is considered as a rapid and accurate tool for identification of fungal pathogens [26]. Genetic variation within ITS region is considered to be sufficient for identification and typing of different fungal strains [27][28][29]. Azoles and allylamines (terbinafine) act as antifungal agents by inhibition of ergosterol biosynthesis while polyenes (nystatin) disrupt cell functions by binding to ergosterol in plasma membrane [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was discarded and the pellet was re‐suspended to create a measured volume of 500 μ L. Due to the high salt content of the catholyte solution, a freeze‐thaw process was applied to the samples instead of using a commercial DNA extraction kit. Freeze‐thaw protocols have been suggested as a method to extract and purify DNA quickly and efficiently, without the need for chemicals . The samples were stored in a –80 °C freezer for three minutes, adjusted to room temperature, and incubated in a 95 °C heated block for two minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Capillary electrophoresis has been previously described in some studies (31,32,33,36) as a promising method for clinically important fungi detection, identification, and differentiation of closely related species. Turenne et al (31) first reported the application of this approach for a large number of commercially available strains and approximately 26 clinical strains, including 12 different Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is based on PCR with panfungal-or genusspecific primers targeting conserved rRNA regions, followed mostly by sequencing (23) or also by other techniques like restriction analysis (restriction fragment length polymorphism [RFLP]) (24), high-resolution melting (HRM) analysis (25,26,27), microarray-based detection (28, 29), pyrosequencing (30), or determination of amplicon size by using capillary electrophoresis (31,32,33). Capillary electrophoresis has been proven to be superior to classical electrophoresis for separating DNA due to its higher efficiency, higher speed, better sensitivity, and better suitability for automation (34).…”
mentioning
confidence: 99%